AVIATION LEGAL ISSUES IN INDONESIA AND THAILAND: TOWARDS BETTER PASSENGERS’ RIGHTS IN ASEAN - Nugraha, Ridha Aditya; Kovudhikulrungsri, Lalin (UI Scholars Hub, 2017)
The aviation business in the ASEAN region has shown significant growth during the last decade. With the enactment of ASEAN Open Skies, there is no doubt that intra-ASEAN flights will continue to increase rapidly with Indonesia and Thailand experiencing significant effects from such development. Considering current rapid market capitalization, there is an urgency to establish equilibrium between commercial and passengers’ rights. Flight delays, cancellations, and denied boarding, either on domestic or international flights, are the main airline passengers’ rights issues that are always relevant and must be kept up-to-date with recent developments. In the context of the so-called integrated ASEAN skies, the urgency to establish a uniform legal framework on passengers’ rights has become essential. Learning from the current international legal framework, namely the Warsaw Convention, the Montreal Convention, and EU Regulation No. 261/2004, they could present the source of best solution. Considering that the latter was established by another regional initiative, it could be a particularly valuable guide for ASEAN, even though the current integration level of the EU and ASEAN are quite different. Also of importance, the bomb threat hoax phenomenon within Indonesia and Thailand shall also be discussed. Passengers’ rights must also be protected against the implications of such irresponsible acts.